2019
DOI: 10.1002/jcp.28961
|View full text |Cite
|
Sign up to set email alerts
|

Copper promotes the migration of bone marrow mesenchymal stem cells via Rnd3‐dependent cytoskeleton remodeling

Abstract: The motility of mesenchymal stem cells (MSCs) is highly related to their homing in vivo, a critical issue in regenerative medicine. Our previous study indicated copper (Cu) might promote the recruitment of endogenous MSCs in canine esophagus defect model. In this study, we investigated the effect of Cu on the motility of bone marrow mesenchymal stem cells (BMSCs) and the underlying mechanism in vitro. Cu supplementation could enhance the motility of BMSCs, and upregulate the expression of hypoxia-inducible fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
3
21
0
1
Order By: Relevance
“…It is probable that this effect was due to higher secretion of CXCL12 as these results are in agreement with the increased secretion of this chemokine after treatment with CuSO 4 (Proteome Profiler analysis, Figure 5). These results find confirmation in the latest findings of Chen et al showing that copper supplementation enhances migration on bone marrow-derived mesenchymal stromal cells [32]. The authors demonstrated that the action of cupric sulfate is associated with the cytoskeleton remodeling induced by hypoxia-inducible factor 1α-(Hif1α-) dependent upregulation of the rho family GTPase 3 (Rnd3).…”
Section: Discussionsupporting
confidence: 77%
“…It is probable that this effect was due to higher secretion of CXCL12 as these results are in agreement with the increased secretion of this chemokine after treatment with CuSO 4 (Proteome Profiler analysis, Figure 5). These results find confirmation in the latest findings of Chen et al showing that copper supplementation enhances migration on bone marrow-derived mesenchymal stromal cells [32]. The authors demonstrated that the action of cupric sulfate is associated with the cytoskeleton remodeling induced by hypoxia-inducible factor 1α-(Hif1α-) dependent upregulation of the rho family GTPase 3 (Rnd3).…”
Section: Discussionsupporting
confidence: 77%
“…Further, emerging evidence has indicated that copper stabilizes the HIF-1α protein through inhibiting prolyl hydroxylases-mediated prolyl hydroxylation in an ironindependent manner, which is required for transcriptional activation of HIF-1 of a series of target genes (Martin et al, 2005;Feng et al, 2009;Himoto et al, 2016;Liu et al, 2018;Chen et al, 2020), suggesting that appropriate copper levels may be required for normal cartilage function through regulation of HIF-1α transcriptional activity. However, detailed mechanisms of transcriptional processes initiating specific target genes expression of HIF-1 require further elucidation.…”
Section: Chondroprotective Effects Of Copper In Cartilagementioning
confidence: 99%
“…HIF-1α regulates SDF-1 expression, and theoretically, Cu also upregulates HIF-1α to increase SDF-1 levels indirectly. Chen found that Cu increased BMSCs motility and recruitment through Rnd3 pathway-dependent cytoskeletal remodeling ( Chen et al, 2020 ). Hence, we designed a composite scaffold by doping Cu into Li-nHA to enhance tissue regeneration potential through the MSCs homing.…”
Section: Discussionmentioning
confidence: 99%